Study Investigation on Pyrolysis of Shivee Ovoo Coal from Mongolia - Batbileg, S.; Purevsuren, B.; Batkhishig, D.; Ankhtuya, A.; Battsetseg, M.; Namkhainorov, J. (Current Advances in Chemistry and Biochemistry Vol. 10, 2021)
The goal of our current research on Shivee Ovoo coal was to characterise the initial coal as well as its hard and liquid products after pyrolysis. To begin with, proximal and ultimate analyses of Shivee Ovoo coal have revealed that it is an oxidised brown coal of the lignite type with the B2 mark. The thermal degradation process of Shivee Ovoo coal was investigated using a thermogravimetric analyzer, which for the first time determined the thermal stability of the coal sample by determining thermal indices from the TG curve, such as T5% -71.85°C; T15% -321.18 °C; T25% -490.64°C from the TG curve, which are the characteristics of lower thermal stability. The yields of produced hard, liquid, and gas products were determined by pyrolysis of Shivee Ovoo coal at various heating temperatures. The most suitable heating temperature was 500°C, which resulted in a higher yield of condensed liquid product -6.28 percent (tar). The yield of all liquid (tar and pyrolysis water) and gas products (44%) indicates that the coal organic material underwent intense thermal decompositions with a greater degree of conversion. This confirms the previously stated and determined reduced thermal stability characteristics of Shivee-Ovoo coal, indicating that it is better suited for gasification and liquefaction. In addition, the yield of hard product (semi-coke) is 56.48 percent at 500oC, which is an important product of the pyrolysis of Shivee Ovoo coal, and its proximate analysis results show that the volatile matter content decreased three times and the caloric value increased by 1000 kcal/kg when compared to the initial coal sample, indicating that it can be used as a smokeless fuel. The chemical composition of pyrolysis tar in group organic compounds obtained by chemical analysis shows that the tar consists largely of neutral oils (81.9%), asphalteines (13.6%), free carbons (3.93%), and organic bases, organic acids, and phenolic compounds (less than 1.0%). The tar was also distilled at room temperature, yielding several fractions with varying boiling temperatures, including a yellow colored light fraction -15.93% (18-180°C), a brown colored middle fraction -15.44% (180 -330°C) and ablack colored heavy fraction -44.53% (330°C>). In compared to the initial coal sample, scanning electron microscopes (SEM) images of generated activated carbon from pyrolyzed hard residue are different.The original coal sample's SEM picture shows compact solid pieces. In comparison to the initial coal sample, the SEM image of carbonised and activated coal sample shows a porosity structure with meso and macro pores. GC/MS analysis was used to investigate the solubility and chemical composition of neutral oil isolated from Shivee Ovoo coal pyrolysis tar, which yielded a total of 68 peaks (signals) for the soluble in hexane, 100 peaks for the soluble in toluene, and 100 peaks for the soluble in a mixed solvent of methylene chloride and methanol (1:1 volume ratio) fractions. Have been determined and identified 22 organic compounds soluble in hexane, 45 organic compounds soluble in toluene and 21 organic compounds soluble in a mixed solvent of methylene chloride and methanol fractions from each related totally registered peaks. On the basis of proximate and ultimate analysis have been confirmed that the Shivee Ovoo coal is a low-rank lignite coal of B2 mark and it is suitable for thermal processing including pyrolysis.